Evaluating research methodology for people who need to read research - Dane, Francis C. 1952- (Sage, 2018)
"The Second Edition offers readers a straightforward presentation of the key components of research and the skills they need to read and evaluate it. The book covers a range of research that students are most likely to encounter, from experimental to field research, and archival to evaluation research. The Second Edition features updated examples of research across disciplines, new and updated content on qualitative research and conceptual statistics, and a streamlined organization that better aligns with the order of information in a research article." -- Provided by publisher.